Factors Associated with Physician Assistant Practice in Rural and Primary Care in Utah. (3rd August 2011) - Coombs, Jennifer M.; Morgan, Perri; Pedersen, Donald M.; Koduri, Sri; Alder, Stephen C.
Abstract : Physician Assistants (PAs) have become an integral part of the United States (U.S.) health care system since the profession began in the late 1960s. PAs have been suggested as solutions to predicted physician shortages especially in primary care. This study examined the predictors of primary care and rural practice patterns of PAs in Utah. A cross sectional survey design was utilized. The outcome variables were practice specialty and practice location. The predictor variables were age, gender, number of years in practice, location of upbringing, and professional school of graduation. There was a response rate of 67.7%. The Utah Division of Occupational and Professional Licensing (DOPL) provided the list of licensed PAs in the state. Physician assistants who reported being raised in rural communities were 2.29 times more likely to be practicing in rural communities (95% CI 0.89–5.85). Female PAs had lower odds of practicing in a rural area (OR: 0.26; 95% CI: 0.10–0.66). Female PAs had lower odds of practicing in primary care versus their male counterparts (OR: 0.56; 95% CI: 0.33–0.96). Graduation from the Utah PA Program was more likely to result in primary care practice (OR: 2.16; 95% CI: 1.34–3.49).